Effectiveness of an Education Program on the Knowledge of the Residents of Geriatric-Care Homes about Personal Hygiene - Ibrahim, Ali Rose; Bakey, Serwan J. (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): Determination effectiveness of the education program on the elderly knowledge about personal hygiene and to find out the relationship between elderly knowledge and their demographic characteristics. Methodology: A quasi-experimental design is done at Al Cyelakh Elderly Care, the study started from 28 April 2022 to 3March 2023. A non-probability purposive sample of (30) elderly lived in the geriatric care home was selected for the purpose of the study. The program and questionnaire was constructed based on extensive review of literature. The instrument’s reliability was determined to be (0.88) using Cronbach’s Alpha. The Validity was established through (10) specialists’ experts. The data were collected by direct interview and questionnaire. Data were analyzed by using (SPSS) package version 25. Descriptive data through determination of: Frequency, percentage, mean of score and standard deviation. Inferential statistical data analysis approach: used by enforcement of the ANOVA T-Test used for determining the relation between Socio-demographic characteristics and adults’ knowledge. Results: The elderly knowledge about personal hygiene was moderate, and no significant relationship between elderly knowledge and their demographic characteristics. Conclusions: The study confirmed the effectiveness of the education program on knowledge of elderly living in Geriatric Home about their personal hygiene. Recommendations: Using the program as a guide for the personal hygiene by geriatric homes residents. Education program, Knowledge, Geriatric Home. Elderly, Personal hygiene. Recommendations: The study recommends to providing a guide line for the personal hygiene in all geriatric care homes.